Allergic bronchopulmonary aspergillosis presenting with a pulmonary mass mimicking lung cancer. Issue 1 (29th July 2013) - Takeuchi, Yohei; Shirai, Toshihiro; Sakurai, Shogo; Mikamo, Masashi; Fujii, Masato; Suda, Takafumi
Abstract A 48‐year‐old man with a history of asthma visited our hospital for the investigation of a high density mass at the right hilum. Laboratory data revealed elevated serum carcinoembryonic antigen. A bronchoscopy was performed to rule out lung cancer; however, mucoid impaction was found without malignant or bacterial cells. On the basis of peripheral blood eosinophilia, elevated total serum IgE, and immediate cutaneous reactivity to Aspergillus fumigatus, he was diagnosed with allergic bronchopulmonary aspergillosis. The radiographic findings and serum carcinoembryonic antigen levels improved with corticosteroids. Pulmonary masses are uncommon findings and serum carcinoembryonic antigen may be a useful marker of the disorder.